Membaca Ulang Kisah Natal dari Bingkai Spiritualitas Pentakosta - Manurung, Kosma (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2021)
Christmas is a celebration commemorating the birth of the Lord Jesus which in the Bible record is a story whose beginning was in God's plan long before the event itself occurred. By using a descriptive analysis approach and literature review, this research intends to offer a perspective on the Christmas story from the Pentecostal spirituality frame. This article contains several examples of the idea of Christmas in the Bible both in the Old Testament and reviews the first Christmas story in the New Testament and also the meaning of Christmas in the context of Pentecostal spirituality. It is concluded that Christmas is the fulfillment of God's promise, Christmas is about divine reconciliation, Christmas also talks about mission, and Christmas is God's means to restore the effects of sin. Natal adalah sebuah perayaan memperingati kelahiran Tuhan Yesus yang dalam catatan Alkitab merupakan sebuah kisah yang permulaannya sudah ada dalam rencana Allah jauh sebelum peristiwa itu sendiri terjadi. Dengan menggunakan pendekatan deskriptif analisis dan kajian literatur penelitian ini bermaksud menawarkan sebuah sudut pandang tentang kisah natal dari bingkai spritualitas Pentakosta. Artikel ini berisikan beberapa contoh ide natal dalam Alkitab baik di Perjanjian Lama maupun ulasan kisah natal pertama di Perjanjian Baru dan juga arti natal dalam bingkai spritulitas Pentakosta. Disimpulkan bahwa natal adalah pengenapan janji Allah, natal berintikan tentang rekonisiali ilahi, natal juga berbicara tentang misi, dan natal menjadi sarana Allah untuk memulihkan dampak dosa.